A study on zoonotic tuberculosis in selected rural areas of Bagalkot and Belgaum districts of Karnataka state. (December 2017) - Dabade, Gopal; Kale, Ashok; Athani, B R; Sankri, Venkatesh; Pawar, S L; Megeri, S N
Abstract: The close association of cattle/buffaloes to farmers and their family members is a well-known phenomenon in rural India. Cattle are major contributors to the income for the sustenance of families, and for many landless farmers, often the only source of livelihood. The animals are sheltered under the same roof where the family members sleep, cook and eat. This close proximity of humans to cattle/buffaloes exposes farmers and family members to tuberculosis (TB), especially if they are vulnerable (e.g. malnourished children along with adults, diabetics, people with HIV/AIDS, people with addiction to alcohol, or smokers) . Several studies have examined the risk factors that are associated with TB, such as crowding (slum dwellers), poor living conditions, alcohol, and tobacco . Other studies have found a significant proportion of diabetic patients with coexistent TB. This study examines the spread of TB from animals to humans and its public health significance. To achieve this, selected numbers of cattle/buffaloes were tested for TB and the association with humans and animals was examined.